Wine phenolics: looking for a smooth mouthfeel - António, M. Jordão (2016)
Each grape variety has its own phenolic profile. However, the concentration of the phenolic compounds present in wine mainly dependson winemaking processes. Phenolic compounds influence wine sensorial characteristics namely taste or mouthfeel, bitterness, astringency and color. Humans can perceive six basic tastes: sweet, salty; sour; umami; fat-taste and bitter taste. This last basic taste is considered as a defense mechanism against the ingestion of potential poisons. Some of the genes,encoding G-protein-coupled receptors - TAS2Rs, which translate for these distinct bitter compounds detectors have been identified. Different phenolic compounds activate distinguished combination of TAS2Rs. Astringency in wine is primarily driven by proanthocyanidins, soluble protein-proanthocyanidins complexes which diminish the protective salivary film and bind to the salivary pellicle; insoluble protein proanthocyanidins complex and proanthocyanidins are rejected against salivary film and trigger astringency sensation via increasing friction. Thus, the aim of this review is to expand the knowledge about the role of wine phenolic compounds in wine sensorial properties, namely in bitterness and astringency phenomenon’s.